Preparation of acetazolamide composite microparticles by supercritical antisolvent techniques - Duarte, Ana Rita C. (2007)
The possibility of preparation of ophthalmic drug delivery systems using compressed anti-solvent technology was evaluated. and RL 100 were used as drug carriers, acetazolamide was the model drug processed. Compressed anti-solvent experiments were carried out as a semi-continuous or a batch operation from a liquid solution of polymer(s) + solute dissolved in acetone. Both techniques allowed the recovery of composite particles, but the semi-continuous operation yielded smaller and less aggregated populations than the batch operation. The release behaviour of acetazolamide from the prepared microparticles was studied and most products exhibited a slower release than the single drug. Moreover, the release could be controlled to some extent by varying the ratio of the two Eudragit used in the formulation and by selecting one or the other anti-solvent technique. Simple diffusion models satisfactorily described the release profiles. Composites specifically produced by semi-continuous technique have a drug release rate controlled by a diffusion mechanism, whereas for composites produced by the batch operation, the polymer swelling also contributes to the overall transport mechanism.